Risk factors for post-partum hemorrhage in patients who underwent operative vaginal delivery in a tertiary care center - Sivasambu, Gayatri Devi; Kempaiah, Sujani B.; Thukral, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Operative vaginal delivery is a timely intervention to cut short second stage labor when imminent delivery is in the interests of mother, fetus, or both. It reduces second stage cesarean section morbidity and uterine scar and its influence on future obstetric career. The possible structural neonatal adverse outcomes due to operative vaginal delivery are well quantified. However, its effects on maternal outcome need to be understood better. In this paper, we study the effect of operative vaginal delivery on maternal post-partum hemorrhage (PPH) and the associated risk factors. Methods: It was a retrospective study carried out for the period July 2016 to July 2020 at Ramaiah Medical College, Bengaluru. Total number of vaginal deliveries in this period were 6318. Out of these, 1020 patients underwent assisted vaginal delivery using vacuum/ forceps/ sequential use of instrument. Blood loss greater than 500 ml is considered PPH for the purpose of this study. 15% of the study population was noted to have PPH. We employ a multivariate logistic regression to identify statistically significant risk factors for PPH in women undergoing operative vaginal delivery. Results: The logistic regression model identifies multiparity, maternal age, neonatal birth weight more than 3.5 kg, application of forceps in women with hypertensive disorders, III-degree tear, cervical tear to significantly increase the risk of PPH in our study population. Conclusions: Certain factors seem to increase the risk of PPH in operative vaginal delivery. The risks and benefits must be weighed properly before use of instruments.